Nigārishāt-i Ārzū Jalīlī - Jalīlī, Ārzū, 1906-1941.; Maz̤har Imām, 1930- (Naʼī Dihlī : Nirālī Dunyā Pablīkeshanz, 2001)
Chiefly on Urdu literature; includes editorial introduction.
Mode of access: Internet.
In Urdu.
Keywords: Urdu literature -- History and criticism